2006
DOI: 10.1007/s00464-005-0429-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic subtotal splenectomy in hereditary spherocytosis

Abstract: Subtotal splenectomy appears to control hemolysis while maintaining splenic function. The laparoscopic approach is safe and effective and should be considered the procedure of choice in hereditary microspherocytosis. Laparoscopic subtotal splenectomy presents an advantage over open subtotal splenectomy, resulting in decreased blood loss, shorter hospital stay, no conversions, fewer operative and postoperative complications, and excellent remission rates. On the basis of our experience, the preservation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…(26,29) Vasilescu et al (24,30) have shown that preservation of the lower pole of the spleen allows a better mobilization of the splenic remnant, and a more accurate assessment of the volume. The length of the splenic remnant ranged between 3.5 and 6 cm, depending on the initial size of the spleen.…”
Section: The Role Of Splenectomy In Hereditary Spherocytosismentioning
confidence: 99%
“…(26,29) Vasilescu et al (24,30) have shown that preservation of the lower pole of the spleen allows a better mobilization of the splenic remnant, and a more accurate assessment of the volume. The length of the splenic remnant ranged between 3.5 and 6 cm, depending on the initial size of the spleen.…”
Section: The Role Of Splenectomy In Hereditary Spherocytosismentioning
confidence: 99%
“…In the past decades, spleen preserving strategies became the preferred treatment options for hemodynamically stable patients with splenic injuries, various splenic tumors and hematological diseases (8,(64)(65)(66)(67)(68). These approaches emerged in order to reduce the infectious and non-infectious complications after splenectomy.…”
Section: Future Perspectives Future Perspectivesmentioning
confidence: 99%
“…Partial splenectomy can be performed by laparoscopic techniques (18, 19). However, the laparoscopic approach is more frequently used for non-traumatic indications and elective operations (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, the laparoscopic approach is more frequently used for non-traumatic indications and elective operations (19). In trauma patients, laparoscopy is uncommon due to the unstable hemodynamic conditions of the patient.…”
Section: Discussionmentioning
confidence: 99%